2019
DOI: 10.1002/cam4.2701
|View full text |Cite
|
Sign up to set email alerts
|

Medulloblastoma has a global impact on health related quality of life: Findings from an international cohort

Abstract: Background: Understanding the global impact of medulloblastoma on health related quality of life (HRQL) is critical to characterizing the broad impact of this disease 448 | and realizing the benefits of modern treatments. We evaluated HRQL in an international cohort of pediatric medulloblastoma patients. Methods: Seventy-six patients were selected from 10 sites across North America, Europe, and Asia, who participated in the Medulloblastoma Advanced Genomics International Consortium (MAGIC). The Health Utilitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…A total of 14 studies are cross-sectional, 15 studies are longitudinal, and 1 study uses both longitudinal and cross-sectional data collection. Articles are included from the United States [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ], Switzerland [ 30 , 31 , 32 , 33 ], South Korea [ 34 , 35 ], Canada [ 36 , 37 ], Japan [ 38 , 39 ], Netherlands [ 40 , 41 ], India [ 42 ], United Kingdom [ 43 , 44 ], Germany [ 45 ], Brazil [ 46 ], Italy [ 47 ], Poland [ 48 ], North American collaboration [ 49 ], European collaboration, [ 50 ] and an international collaborative [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 14 studies are cross-sectional, 15 studies are longitudinal, and 1 study uses both longitudinal and cross-sectional data collection. Articles are included from the United States [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ], Switzerland [ 30 , 31 , 32 , 33 ], South Korea [ 34 , 35 ], Canada [ 36 , 37 ], Japan [ 38 , 39 ], Netherlands [ 40 , 41 ], India [ 42 ], United Kingdom [ 43 , 44 ], Germany [ 45 ], Brazil [ 46 ], Italy [ 47 ], Poland [ 48 ], North American collaboration [ 49 ], European collaboration, [ 50 ] and an international collaborative [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…A total of 11 studies analyse individual diagnoses, whilst 12 combine several different CNS diagnoses within their analyses. Eight studies analyse the HRQoL in patients diagnosed with a tumour of the brainstem or cerebellum (including medulloblastoma [ 22 , 43 , 47 , 50 , 51 ], diffuse intrinsic pontine glioma [ 28 , 40 ], or atypical teratoid rhabdoid tumour [ 32 ]. Kamran et al (2018) describe self-reported increases in HRQoL annually for a median of 5 years post-PRT [ 22 ], whilst Veldhuijzen van Zanten et al (2017) survivors self-reported worsening in nausea and fear of procedures at 3 months post-XRT [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…This improvement was led through continuous progression in understanding the biological mechanisms behind this cancer and strengthened by emerging technologies and treatments. Although this OS sounds very positive, the reality of the age of these patients, coupled with the harsh quality of life (QOL) observed after the treatments ( 84 , 85 ) pushes this scientific field to develop more novel and targeted therapies which can ameliorate the dismal QOL.…”
Section: The Role Of Mycn In the Origin Of Medulloblastomamentioning
confidence: 99%
“…Pediatric populations diagnosed with medulloblastomas comprise 15%-20% of all brain tumors [ 2 ]. Unfortunately, the quality of life for many of these children severely deteriorates despite high survival rates with aggressive chemotherapy, radiotherapy, and neurosurgery [ 3 ]. Due to the prevalence of medulloblastomas situated in the posterior fossa, they often rapidly metastasize into the cerebrospinal fluid and affect different parts of the brain, aside from the infratentorial region [ 4 ].…”
Section: Introductionmentioning
confidence: 99%